A vulnerability paradox in the cross-national prevalence of post-traumatic stress disorder - Dückers, Michel L. A.; Alisic, Eva; Brewin, Chris R. (British journal of psychiatry, 2016)
Determinants of cross-national differences in the prevalence of mental illness are poorly understood. To test whether national post-traumatic stress disorder (PTSD) rates can be explained by (a) rates of exposure to trauma and (b) countries' overall cultural and socioeconomic vulnerability to adversity. We collected general population studies on lifetime PTSD and trauma exposure, measured using the WHO Composite International Diagnostic Interview (DSM-IV). PTSD prevalence was identified for 24 countries (86 687 respondents) and exposure for 16 countries (53 038 respondents). PTSD was predicted using exposure and vulnerability data. PTSD is related positively to exposure but negatively to country vulnerability. Together, exposure, vulnerability and their interaction explain approximately 75% of variance in the national prevalence of PTSD. Contrary to expectations based on individual risk factors, we identified a paradox whereby greater country vulnerability is associated with a decreased, rather than increased, risk of PTSD for its citizens.